The impact of standard protocol implementation on the quality of colorectal cancer pathology reporting - Ihnát, Peter; Delongová, Patricie; Horáček, Jaroslav; Ihnát Rudinská, Lucia; Vávra, Petr; Zonča, Pavel (World journal of surgery, 2015)
BACKGROUND: The aim of the study is to assess the influence of standardized protocol implementation on the quality of colorectal cancer histopathology reporting. METHODS: A standardized protocol was created based on the recommendations of The College of American Pathologists. The impact of this protocol was measured by comparing frequencies of assessed parameters in histopathology reports before and after implementation. RESULTS: In total, 177 histopathology reports were included in this study. The numbers of harvested lymph nodes were 12.4 ± 5.2 (colon) and 12.6 ± 5.4 (rectum) before protocol; and 17.1 ± 6.5 (colon), and 16.6 ± 7.0 after protocol implementation; differences were statistically significant. The recommended minimum of 12 lymph nodes was not achieved in 42.8 % (colon) and 45.7 % (rectum) of specimens before, and in 10.4 % (colon) and 17.7 % (rectum) of specimens after protocol implementation; differences were statistically significant. There were no differences in histopathology assessment of proximal and distal resection margins, grading assessment, TNM staging recording, and number of positive findings of microscopic tumor aggressiveness. The findings of tumor budding, tumor satellites, and assessment of microscopic tumor aggressiveness were more frequent after protocol implementation. Histopathology reports of rectal specimens contained assessments of the macroscopic quality of mesorectum, circumferential resection margin, and neoadjuvant therapy effect (if administered) only after protocol introduction. CONCLUSIONS: A standardized protocol is a valuable and effective tool for improving the quality of histopathology reporting. Its implementation is associated with more precise specimen evaluation, higher numbers of harvested lymph nodes, and improved completeness of histopathology reports.
Keywords: lymfatické uzliny; Lymph Node Excision; Quality Control; Male; kolorektální nádory; řízení kvality; Lymph Nodes; Neoplasm Staging; Česká republika; chirurgická patologie; lymfadenektomie; Aged; Clinical Protocols; mužské pohlaví; senioři; dokumentace; Czech Republic; lidé; ženské pohlaví; Humans; Colorectal Neoplasms; Pathology, Surgical; Documentation; klinické protokoly; Female; staging nádorů